Geoinformation mapping of the soil cover and land adjacent to the Burshtyn TPP, and recommendations for their environmentally balanced use - Kolesnik, N. (Land Management, Cadastre and Land Monitoring, 2025)
Today, an important task for Ukraine is to assess the condition of land damaged and contaminated by military operations and to restore it. The use of geographic information systems and comprehensive analytical methods has repeatedly proven its effectiveness. In this study, GIS technologies are used to map the condition of land around the Burshtyn Thermal Power Plant in order to study the anthropogenic load on it. Based on remote sensing data, namely satellite images, analytical cartographic sources and scientific publications, thematic maps have been constructed, namely a soil map, three maps of soil contamination with heavy metals (copper, lead, cobalt), and a land map. These maps were developed in the QGIS environment and designed in accordance with standards. Within the zone of influence of the Burshtyn TPP, various types of soils have been identified that react differently to anthropogenic load. Analysis of the spatial distribution of heavy metals has made it possible to clearly identify areas of pollutant accumulation. This will allow for the formation of environmentally safe land use. The results of the study can be used for environmental zoning planning, degraded land management, and the development of sustainable development programmes after the Burshtyn TPP ceases operations. Keywords: Burshtyn TPP, ecology, land condition, soils, GIS technologies, cartography, anthropogenic load.